Diagnostic accuracy of a prototype rapid chlamydia and gonorrhoea recombinase polymerase amplification assay: a multicentre cross-sectional preclinical evaluation. (March 2019) - Harding-Esch, E.M.; Fuller, S.S.; Chow, S.-L.C.; Nori, A.V.; Harrison, M.A.; Parker, M.; Piepenburg, O.; Forrest, M.S.; Brooks, D.G.; Patel, R.; Hay, P.E.; Fearnley, N.; et al.
Abstract: Objectives: Rapid and accurate sexually transmitted infection diagnosis can reduce onward transmission and improve treatment efficacy. We evaluated the accuracy of a 15-minute run-time recombinase polymerase amplification–based prototype point-of-care test (TwistDx) for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG). Methods: Prospective, multicentre study of symptomatic and asymptomatic patients attending three English sexual health clinics. Research samples provided were additional self-collected vulvovaginal swab (SCVS) (female participants) and first-catch urine (FCU) aliquot (female and male participants). Samples were processed blind to the comparator (routine clinic CT/NG nucleic acid amplification test (NAAT)) results. Discrepancies were resolved using Cepheid CT/NG GeneXpert. Results: Both recombinase polymerase amplification and routine clinic NAAT results were available for 392 male and 395 female participants. CT positivity was 8.9% (35/392) (male FCU), 7.3% (29/395) (female FCU) and 7.1% (28/395) (SCVS). Corresponding NG positivity was 3.1% (12/392), 0.8% (3/395) and 0.8% (3/395). Specificity and positive predictive values were 100% for all sample types and both organisms, except male CT FCU (99.7% specificity (95% confidence interval (CI) 98.4–100.0; 356/357), 97.1% positive predictive value (95% CI 84.7–99.9; 33/34)). For CT, sensitivity was ≥94.3% for FCU and SCVS. CT sensitivity for female FCU was higher (100%; 95% CI, 88.1–100; 29/29) than for SCVS (96.4%; 95% CI, 81.7–99.9; 27/28). NG sensitivity and negative predictive values were 100% in FCU (male and female). Conclusions: This prototype test has excellent performance characteristics, comparable to currently used NAATs, and fulfils several World Health Organization ASSURED criteria. Its rapidity without loss of performance suggests that once further developed and commercialized, this test could positively affect clinical practice and public health.